The Legality of Online Marriage in Islamic Family Law - Ubaidillah Cholil (Rechtsvinding, 2025)
Advancements in information and communication technology have transformed many dimensions of human life, including the field of Islamic family law. One significant implication of this development is the emergence of online marriage practices, in which the ijab and qabul are conducted through virtual media such as video calls. This practice is commonly adopted due to geographical distance, emergency situations such as pandemics, or other specific considerations. Despite the convenience it offers, online marriage has generated debate regarding the validity of the marriage contract under Islamic law and its legal recognition within the national legal system. This article aims to analyze the response of Islamic family law to digitalization through the practice of online marriage, while also examining its legal validity by reviewing classical fiqh perspectives and the relevant statutory regulations in Indonesia.